40-fs hydrogen Raman laser. (28th December 2015) - Didenko, N V; Konyashchenko, A V; Kostryukov, P V; Losev, L L; Pazyuk, V S; Tenyakov, S Yu; Molchanov, V Ya; Chizhikov, S I; Yushkov, K B
Abstract: 40-fs first Stokes pulses at a wavelength of 1.2 μm were generated in a hydrogen SRS-converter pumped by orthogonally polarised double chirped pulses of a Ti : sapphire laser. To obtain a Stokes pulse close to a transform-limited one, a programmed acousto-optic dispersive delay line was placed between the master oscillator and regenerative amplifier. The energy efficiency of Stokes radiation conversion reached 22%.